The sensitivity status of community-acquired Staphylococcus aureus isolated from various infectious sites in Kano-City, Nigeria to selected antibacterial agents (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Community acquired Staphylococcus aureus was isolated from various infectious sites in two private laboratories in Kano-city, Nigeria. A total of 247 (11%) Staphylococcu aureus isolates were recovered from all infectious sites except cerebro-spinal fluid. The least Staphylococcus aureus isolates were found in urine specimens (5.4%). Twenty three (23) out of 62 (37.1%) and 10 out of 26 (38.5%) of the wound and pus specimens respectively incriminated Staphylococcus aureus as the major pathogens. High resistance rates were recorded with ciprofloxacin (55%), chloramphenicol (76.4%), amoxicillin (81.8%), nitrofurantoin (84.2%), erythromycin (93.1%), cotrimoxazole (94.3%), tetracycline (94.7%) and nalidixic acid (96.8%) but ofloxacin, co-amoxiclav, gentamicin and ceftriaxone showed moderate activity. The widespread resistance of community acquired Staphylococcus aureus was worst with the older antibacterial agents possibly due to their indiscriminate use after existence in the market for long. Thus, many older generation antibacterial agents are not appropriate for chemotherapy of community acquired Staphylococcus aureus infections.
Keywords: Sensitivity status; Community-acquired infection; Staphylococcus aureus; Kanocity